High-strength pervious concrete and preparation method thereof

By using raw materials such as basalt gravel, ceramide, modified steel fibers and toughening thickeners, high-strength permeable concrete is prepared, which solves the problem of insufficient mechanical properties of existing permeable concrete and achieves efficient permeable and frost resistance in cold areas.

CN119874268APending Publication Date: 2025-04-25TIANYUAN CONSTR GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510028869.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing water permeable concrete is difficult to ensure high mechanical properties while ensuring water permeability, especially in cold areas, which is insufficient in freezing resistance, which affects its stability and application range.

Method used

High-strength permeable concrete is prepared by using raw materials such as basalt gravel, ceramics, modified steel fibers and toughening thickeners through specific ratios and processes. Modified steel fibers enhance strength through acidification modification and nanocarbon black deposition, while toughening thickeners improve the adhesion of aggregates and slurries.

Benefits of technology

While maintaining water permeability, the compressive strength, flexural strength and frost resistance of concrete are significantly improved, and its applicability and stability in cold areas are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874268A_ABST
    Figure CN119874268A_ABST
Patent Text Reader

Abstract

The invention discloses high-strength pervious concrete and a preparation method thereof, and belongs to the technical field of concrete. The high-strength pervious concrete is prepared from the following raw materials: basalt macadam, ceramsite, cement, water, mineral powder, reinforced fibers, a toughening and thickening agent and a water reducing agent. According to the invention, firstly, steel fibers are modified, and the adding proportion is optimized, so that the optimization of increasing the strength of the concrete is realized; a toughening and thickening agent composed of tripropylene glycol monomethyl ether, hydroxyethyl acrylate and yellow dextrin is further added, the adhesiveness between aggregate and slurry is improved, weak interfaces generated in concrete when coarse aggregate is used are reduced, and under the condition that water permeability is guaranteed, the bonding strength is improved, and meanwhile the strength of the concrete is enhanced. The modified steel fiber and the toughening enhancer are combined for use, so that the defect of low strength of the pervious concrete is overcome, and the pervious concrete is excellent in mechanical strength and good in water permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and particularly relates to high-strength permeable concrete and a preparation method thereof. Background Art

[0002] Sponge city is a systematic concept, which requires comprehensive design of regional precipitation analysis, urban design, permeable concrete, permeable base and drainage scheme to ensure the realization of sponge city. Permeable concrete is the material basis for the construction of sponge city, which can be used in the construction of pedestrian walkways, urban squares and highway pavements. With the in-depth experimental research on permeable concrete, its application has received more and more attention.

[0003] Permeable concrete is a porous lightweight concrete with high porosity, which is mainly composed of a mixture of coarse aggregate, cement and water, and does not contain fine aggregate. This kind of concrete forms a honeycomb structure by wrapping a thin layer of cement slurry on the surface of the coarse aggregate, so that it has good air permeability and water permeability. Permeable concrete is a new type of concrete material with excellent water permeability, good environmental protection performance and heat dissipation performance. Due to its excellent water permeability, it can effectively alleviate the local water accumulation and waterlogging problems in the city, and it can realize the secondary reuse of natural water resources in conjunction with the urban rainwater recycling system. Although permeable concrete is currently being promoted and applied, at present, permeable concrete has good water permeability. At the same time, due to its porous skeleton pore structure, the grading, size, and mortar-bone ratio of aggregates will affect the strength, making it difficult to ensure high mechanical properties, which seriously affects the application scope of permeable concrete.

[0004] In addition, in winter, when the temperature drops below freezing, the water in the pervious concrete will freeze, causing the pore structure to be destroyed, which in turn affects its overall stability and drainage capacity. Therefore, studying the antifreeze performance of pervious concrete is crucial to improving its applicability in cold regions. By exploring ways to improve antifreeze performance, such as optimizing material ratios and improving construction processes, technical support can be provided for the widespread application of pervious concrete in cold regions.

[0005] Therefore, in order to ensure the construction quality of permeable concrete, the proportion of various raw materials must be accurately controlled to ensure the best results. Select the appropriate coarse aggregate particle size and accurately control the water content and proportion of the cement paste to meet the permeability requirements. At the same time, consider the workability of permeable concrete and reasonably set the amount of cement added to avoid the adverse effects of insufficient or excessive cement on performance. At the same time, in order to improve the application value, fibers can be added to the material to enhance the tensile strength and improve the mechanical properties of concrete. Summary of the invention

[0006] The object of the present invention is to provide a high-strength permeable concrete which can have excellent mechanical strength while ensuring water permeability.

[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:

[0008] A high-strength permeable concrete comprises the following raw materials: 1200-1300 parts of basalt crushed stone, 200-220 parts of ceramsite, 300-350 parts of cement, 100-110 parts of water, 70-80 parts of mineral powder, 52-64 parts of reinforcing fiber, 12-16 parts of toughening and thickening agent, and 1.5-3 parts of water reducing agent.

[0009] Furthermore, the basalt gravel has a particle size of 10-15 mm, and the expanded clay is shale expanded clay with a particle size of 5-10 mm.

[0010] Furthermore, the toughening and thickening agent includes tripropylene glycol methyl ether, hydroxyethyl acrylate, and yellow dextrin, and the solid-liquid ratio of the three is 1L:1L:1kg.

[0011] Furthermore, the reinforcing fiber is a modified steel fiber; and the water reducer is a high-efficiency polycarboxylate water reducer.

[0012] Furthermore, the modified steel fiber is prepared by the following steps:

[0013] (1) mixing and dispersing nano carbon black, a silane coupling agent, and water to obtain a modified solution;

[0014] (2) The steel fiber was immersed in a 2 mol / L sulfuric acid solution at a solid-liquid ratio of 1:3 to remove impurities, and then fully immersed for 1-2 hours and then washed with deionized water;

[0015] (3) The steel fiber obtained in step (2) is immersed in an ethanol solution with a mass concentration of 50%, and the modified solution in step (1) is added, and stirred to allow the modified solution to be dispersed and adsorbed on the steel fiber, and placed at a high temperature of 120° C. to react for 2-3 hours, and then cooled to room temperature to obtain the modified steel fiber.

[0016] Furthermore, in the step (1), the mass-volume ratio of the nano-carbon black, the silane coupling agent, and the deionized water is (0.3-0.5) kg:1 L:(1-3) L; and the particle size of the nano-carbon black is 60 nm.

[0017] Furthermore, in step (2), the steel fiber has a length of 8-10 mm and a diameter of 0.18-0.23 mm.

[0018] Furthermore, in step (3), the solid-liquid ratio of the steel fiber, the ethanol solution, and the modified solution is 1kg:3L:3L.

[0019] Furthermore, the dispersion treatment in step (1) is ultrasonic dispersion for 15-30 minutes, and the ultrasonic dispersion power is 300-350w.

[0020] Furthermore, the stirring in step (3) is magnetic stirring, stirring at 100 r / min for 10 min.

[0021] A method for preparing high-strength permeable concrete comprises the following steps:

[0022] (1) preparing modified steel fiber and preparing toughening and thickening agent according to the proportion;

[0023] (2) Cement, mineral powder and water are mixed and stirred evenly, and then basalt crushed stone, ceramsite, water reducing agent and modified steel fiber are added in sequence and stirred evenly, and finally a toughening and thickening agent is added and stirred evenly to obtain a final product of high-strength permeable concrete.

[0024] The raw materials used in the present invention are all commercially available.

[0025] Basalt crushed stone can significantly improve the compressive strength, flexural strength and durability of concrete. As a natural volcanic rock, basalt has good environmental characteristics. Its use as concrete aggregate not only consumes industrial waste, but also reduces dependence on natural resources, and has significant economic and environmental advantages.

[0026] Shale expanded clay has a porous structure, and shale expanded clay concrete has high compressive strength. In addition, shale expanded clay has good bonding properties with cement, which can improve the overall durability and corrosion resistance of concrete.

[0027] The present invention acidifies and modifies steel fibers, increases the roughness of the steel fiber surface while removing impurities, and then deposits nano carbon black on the steel fiber surface to further enhance the strength of the material; then adds a silane coupling agent to change the surface properties of the nano carbon black, making it easier to disperse, and improves the bonding force between the nano carbon black and the steel fiber, thereby enhancing the toughness of the concrete. In addition, nano carbon black has a large specific surface area and surface energy, which can allow the steel fiber to form a binding force in the concrete matrix, increase the cohesion of the concrete, and thus effectively resist the effect of external loads, making the concrete more durable.

[0028] The toughening and thickening agent composed of tripropylene glycol methyl ether, hydroxyethyl acrylate and yellow dextrin can increase the adhesion between aggregate and paste and other materials, thereby reducing the weak interface generated inside the concrete when coarse aggregate is used. While ensuring water permeability, the thickening and toughening agent can enhance the compressive strength of concrete while improving the bonding strength.

[0029] Beneficial Effects

[0030] The invention adopts coarse aggregate, gel material, water, reinforcing fiber, toughening and reinforcing agent and the like to stir and form. The difference from ordinary concrete is that fine aggregate is not used, a multi-void structure is formed, the porosity of the concrete is increased, and the water permeability of the concrete is improved.

[0031] The present invention combines modified steel fiber with a toughening and reinforcing agent to make up for the defect of low strength of permeable aggregate and improve the compressive strength and flexural strength of concrete. The concrete obtained by compounding multiple raw materials in a specific proportion has excellent mechanical strength and good permeability, and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Steel fiber photos are used for this invention;

[0033] Figure 2 This is a scanning electron microscope image of the interface between the steel fiber and the slurry in Example 3 of the present invention. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.

[0035] Example 1

[0036] A high-strength permeable concrete comprises the following raw materials: 1200 parts of basalt crushed stone, 200 parts of ceramsite, 300 parts of cement, 100 parts of water, 70 parts of mineral powder, 52 parts of reinforcing fiber, 12 parts of toughening and thickening agent, and 1.5 parts of water reducing agent.

[0037] The particle size of the basalt gravel is 10-15 mm, and the ceramsite is shale ceramsite with a particle size of 5-10 mm.

[0038] The toughening and thickening agent includes tripropylene glycol methyl ether, hydroxyethyl acrylate and yellow dextrin, and the solid-liquid ratio of the three is 1L:1L:1kg.

[0039] The reinforcing fiber is a modified steel fiber; the water reducer is a high-efficiency polycarboxylate water reducer.

[0040] The modified steel fiber is prepared by the following steps:

[0041] (1) mixing nano carbon black, silane coupling agent and water in a mass-volume ratio of 0.3 kg: 1 L: 1 L and ultrasonically dispersing for 15 minutes at an ultrasonic dispersion power of 300-350 W to obtain a modified solution;

[0042] (2) The steel fiber was immersed in a 2 mol / L sulfuric acid solution at a solid-liquid ratio of 1:3 to remove impurities, and then fully immersed for 1-2 hours and then washed with deionized water;

[0043] (3) The steel fiber obtained in step (2) is immersed in an ethanol solution with a mass concentration of 50%, and the modified solution in step (1) is added. The modified solution is dispersed and adsorbed on the steel fiber by magnetic stirring at 100 r / min for 10 min. The solution is placed at a high temperature of 120° C. for reaction for 2-3 h, and then cooled to room temperature to obtain the modified steel fiber.

[0044] The particle size of the nano carbon black is 60nm; the length of the steel fiber is 8-10mm and the diameter is 0.18-0.23mm; the solid-liquid ratio of the steel fiber, ethanol solution and modified solution in step (3) is 1kg:3L:3L.

[0045] A method for preparing high-strength permeable concrete comprises the following steps:

[0046] (1) preparing modified steel fiber and preparing toughening and thickening agent according to the proportion;

[0047] (2) Cement, mineral powder and water are mixed and stirred evenly, and then basalt crushed stone, ceramsite, water reducing agent and modified steel fiber are added in sequence and stirred evenly, and finally a toughening and thickening agent is added and stirred evenly to obtain a final product of high-strength permeable concrete.

[0048] Example 2

[0049] A high-strength permeable concrete comprises the following raw materials: 1250 parts of basalt crushed stone, 210 parts of ceramsite, 320 parts of cement, 105 parts of water, 75 parts of mineral powder, 58 parts of reinforcing fiber, 14 parts of toughening and thickening agent, and 2 parts of water reducing agent.

[0050] The particle size of the basalt gravel is 10-15 mm, and the ceramsite is shale ceramsite with a particle size of 5-10 mm.

[0051] The toughening and thickening agent includes tripropylene glycol methyl ether, hydroxyethyl acrylate and yellow dextrin, and the solid-liquid ratio of the three is 1L:1L:1kg.

[0052] The reinforcing fiber is a modified steel fiber; the water reducer is a high-efficiency polycarboxylate water reducer.

[0053] The modified steel fiber is prepared by the following steps:

[0054] (1) mixing nano carbon black, silane coupling agent and water in a mass-volume ratio of 0.4 kg: 1 L: 2 L and ultrasonically dispersing for 20 minutes at an ultrasonic dispersion power of 300-350 W to obtain a modified solution;

[0055] (2) The steel fiber was immersed in a 2 mol / L sulfuric acid solution at a solid-liquid ratio of 1:3 to remove impurities, and then fully immersed for 1-2 hours and then washed with deionized water;

[0056] (3) The steel fiber obtained in step (2) is immersed in an ethanol solution with a mass concentration of 50%, and the modified solution in step (1) is added. The modified solution is dispersed and adsorbed on the steel fiber by magnetic stirring at 100 r / min for 10 min. The solution is placed at a high temperature of 120° C. for reaction for 2-3 h, and then cooled to room temperature to obtain the modified steel fiber.

[0057] The particle size of the nano carbon black is 60nm; the length of the steel fiber is 8-10mm and the diameter is 0.18-0.23mm; the solid-liquid ratio of the steel fiber, ethanol solution and modified solution in step (3) is 1kg:3L:3L.

[0058] A method for preparing high-strength permeable concrete comprises the following steps:

[0059] (1) preparing modified steel fiber and preparing toughening and thickening agent according to the proportion;

[0060] (2) Cement, mineral powder and water are mixed and stirred evenly, and then basalt crushed stone, ceramsite, water reducing agent and modified steel fiber are added in sequence and stirred evenly, and finally a toughening and thickening agent is added and stirred evenly to obtain a final product of high-strength permeable concrete.

[0061] Example 3

[0062] A high-strength permeable concrete comprises the following raw materials: 1300 parts of basalt crushed stone, 220 parts of ceramsite, 350 parts of cement, 110 parts of water, 80 parts of mineral powder, 64 parts of reinforcing fiber, 16 parts of toughening and thickening agent, and 3 parts of water reducing agent.

[0063] The particle size of the basalt gravel is 10-15 mm, and the ceramsite is shale ceramsite with a particle size of 5-10 mm.

[0064] The toughening and thickening agent includes tripropylene glycol methyl ether, hydroxyethyl acrylate and yellow dextrin, and the solid-liquid ratio of the three is 1L:1L:1kg.

[0065] The reinforcing fiber is a modified steel fiber; the water reducer is a high-efficiency polycarboxylate water reducer.

[0066] The modified steel fiber is prepared by the following steps:

[0067] (1) mixing nano carbon black, silane coupling agent and water in a mass-volume ratio of 0.5 kg: 1 L: 3 L and ultrasonically dispersing for 30 minutes at an ultrasonic dispersion power of 300-350 W to obtain a modified solution;

[0068] (2) The steel fiber was immersed in a 2 mol / L sulfuric acid solution at a solid-liquid ratio of 1:3 to remove impurities, and then fully immersed for 1-2 hours and then washed with deionized water;

[0069] (3) The steel fiber obtained in step (2) is immersed in an ethanol solution with a mass concentration of 50%, and the modified solution in step (1) is added. The modified solution is dispersed and adsorbed on the steel fiber by magnetic stirring at 100 r / min for 10 min. The solution is placed at a high temperature of 120° C. for reaction for 2-3 h, and then cooled to room temperature to obtain the modified steel fiber.

[0070] The particle size of the nano carbon black is 60nm; the length of the steel fiber is 8-10mm and the diameter is 0.18-0.23mm; the solid-liquid ratio of the steel fiber, ethanol solution and modified solution in step (3) is 1kg:3L:3L.

[0071] A method for preparing high-strength permeable concrete comprises the following steps:

[0072] (1) preparing modified steel fiber and preparing toughening and thickening agent according to the proportion;

[0073] (2) Cement, mineral powder and water are mixed and stirred evenly, and then basalt crushed stone, ceramsite, water reducing agent and modified steel fiber are added in sequence and stirred evenly, and finally a toughening and thickening agent is added and stirred evenly to obtain a final product of high-strength permeable concrete.

[0074] Figure 2 This is a scanning electron microscope image of the damaged permeable concrete in Example 3. Figure 2 It can be seen that the cracks between the modified steel fiber and the slurry are extremely small, and a small amount of nano carbon black is attached to the surface of the steel fiber, indicating that the modified steel fiber has good adhesion to the slurry; there are multiple parallel scratches on the surface of the modified steel fiber, indicating that the fiber provided tension when the test block was destroyed here. After adding modified steel fiber and toughening thickener, the workability between the fiber and the slurry is good, and it can be clearly seen that the fiber plays a role in pulling when the test block is destroyed, which improves the bearing capacity of the test block, indicating that the modified steel fiber can play its fiber effect well and improve the mechanical properties of permeable concrete.

[0075] Comparative Example 1

[0076] A high-strength permeable concrete comprises the following raw materials: 1300 parts of basalt crushed stone, 220 parts of ceramsite, 350 parts of cement, 110 parts of water, 80 parts of mineral powder, 64 parts of reinforcing fiber, 16 parts of toughening and thickening agent, and 3 parts of water reducing agent.

[0077] The particle size of the basalt gravel is 10-15 mm, and the ceramsite is shale ceramsite with a particle size of 5-10 mm.

[0078] The toughening and thickening agent includes tripropylene glycol methyl ether, hydroxyethyl acrylate and yellow dextrin, and the solid-liquid ratio of the three is 1L:1L:1kg.

[0079] The reinforcing fiber is a steel fiber; the length of the steel fiber is 8-10 mm and the diameter is 0.18-0.23 mm; the water reducer is a high-efficiency polycarboxylate water reducer.

[0080] A method for preparing high-strength permeable concrete comprises the following steps:

[0081] (1) preparing modified steel fiber and preparing toughening and thickening agent according to the proportion;

[0082] (2) Cement, mineral powder and water are mixed and stirred evenly, and then basalt crushed stone, ceramsite, water reducing agent and modified steel fiber are added in sequence and stirred evenly, and finally a toughening and thickening agent is added and stirred evenly to obtain a final product of high-strength permeable concrete.

[0083] Compared with Example 3, this comparative example is the same as Example 3 except that the steel fiber is not modified.

[0084] Comparative Example 2

[0085] A high-strength permeable concrete comprises the following raw materials: 1300 parts of basalt crushed stone, 220 parts of ceramsite, 350 parts of cement, 110 parts of water, 80 parts of mineral powder, 64 parts of reinforcing fiber, 16 parts of toughening and thickening agent, and 3 parts of water reducing agent.

[0086] The particle size of the basalt gravel is 10-15 mm, and the ceramsite is shale ceramsite with a particle size of 5-10 mm.

[0087] The toughening and thickening agent includes hydroxyethyl acrylate and yellow dextrin, and the solid-liquid ratio of the two is 1L:1kg.

[0088] The reinforcing fiber is a modified steel fiber; the water reducer is a high-efficiency polycarboxylate water reducer.

[0089] The modified steel fiber is prepared by the following steps:

[0090] (1) mixing nano carbon black, silane coupling agent and water in a mass-volume ratio of 0.5 kg: 1 L: 3 L and ultrasonically dispersing for 30 minutes at an ultrasonic dispersion power of 300-350 W to obtain a modified solution;

[0091] (2) The steel fiber was immersed in a 2 mol / L sulfuric acid solution at a solid-liquid ratio of 1:3 to remove impurities, and then fully immersed for 1-2 hours and then washed with deionized water;

[0092] (3) The steel fiber obtained in step (2) is immersed in an ethanol solution with a mass concentration of 50%, and the modified solution in step (1) is added. The modified solution is dispersed and adsorbed on the steel fiber by magnetic stirring at 100 r / min for 10 min. The solution is placed at a high temperature of 120° C. for reaction for 2-3 h, and then cooled to room temperature to obtain the modified steel fiber.

[0093] The particle size of the nano carbon black is 60nm; the length of the steel fiber is 8-10mm and the diameter is 0.18-0.23mm; the solid-liquid ratio of the steel fiber, ethanol solution and modified solution in step (3) is 1kg:3L:3L.

[0094] A method for preparing high-strength permeable concrete comprises the following steps:

[0095] (1) preparing modified steel fiber and preparing toughening and thickening agent according to the proportion;

[0096] (2) Cement, mineral powder and water are mixed and stirred evenly, and then basalt crushed stone, ceramsite, water reducing agent and modified steel fiber are added in sequence and stirred evenly, and finally a toughening and thickening agent is added and stirred evenly to obtain a final product of high-strength permeable concrete.

[0097] Compared with Example 3, this comparative example has the same raw materials and steps as Example 3 except that tripropylene glycol methyl ether is not added as the toughening and thickening agent.

[0098] Comparative Example 3

[0099] A high-strength permeable concrete comprises the following raw materials: 1300 parts of basalt crushed stone, 220 parts of ceramsite, 350 parts of cement, 110 parts of water, 80 parts of mineral powder, 64 parts of reinforcing fiber, 16 parts of toughening and thickening agent, and 3 parts of water reducing agent.

[0100] The particle size of the basalt gravel is 10-15 mm, and the ceramsite is shale ceramsite with a particle size of 5-10 mm.

[0101] The toughening and thickening agent includes tripropylene glycol methyl ether and yellow dextrin, and the solid-liquid ratio of the two is 1L:1kg.

[0102] The reinforcing fiber is a modified steel fiber; the water reducer is a high-efficiency polycarboxylate water reducer.

[0103] The modified steel fiber is prepared by the following steps:

[0104] (1) mixing nano carbon black, silane coupling agent and water in a mass-volume ratio of 0.5 kg: 1 L: 3 L and ultrasonically dispersing for 30 minutes at an ultrasonic dispersion power of 300-350 W to obtain a modified solution;

[0105] (2) The steel fiber was immersed in a 2 mol / L sulfuric acid solution at a solid-liquid ratio of 1:3 to remove impurities, and then fully immersed for 1-2 hours and then washed with deionized water;

[0106] (3) The steel fiber obtained in step (2) is immersed in an ethanol solution with a mass concentration of 50%, and the modified solution in step (1) is added. The modified solution is dispersed and adsorbed on the steel fiber by magnetic stirring at 100 r / min for 10 min. The solution is placed at a high temperature of 120° C. for reaction for 2-3 h, and then cooled to room temperature to obtain the modified steel fiber.

[0107] The particle size of the nano carbon black is 60nm; the length of the steel fiber is 8-10mm and the diameter is 0.18-0.23mm; the solid-liquid ratio of the steel fiber, ethanol solution and modified solution in step (3) is 1kg:3L:3L.

[0108] A method for preparing high-strength permeable concrete comprises the following steps:

[0109] (1) preparing modified steel fiber and preparing toughening and thickening agent according to the proportion;

[0110] (2) Cement, mineral powder and water are mixed and stirred evenly, and then basalt crushed stone, ceramsite, water reducing agent and modified steel fiber are added in sequence and stirred evenly, and finally a toughening and thickening agent is added and stirred evenly to obtain a final product of high-strength permeable concrete.

[0111] Compared with Example 3, this comparative example has the same raw materials and steps as Example 3 except that hydroxyethyl acrylate is not added as the toughening and thickening agent.

[0112] Comparative Example 4

[0113] A high-strength permeable concrete comprises the following raw materials: 1300 parts of basalt crushed stone, 220 parts of ceramsite, 350 parts of cement, 110 parts of water, 80 parts of mineral powder, 64 parts of reinforcing fiber, 16 parts of toughening and thickening agent, and 3 parts of water reducing agent.

[0114] The particle size of the basalt gravel is 10-15 mm, and the ceramsite is shale ceramsite with a particle size of 5-10 mm.

[0115] The toughening and thickening agent includes tripropylene glycol methyl ether and hydroxyethyl acrylate, and the volume ratio of the two is 1:1.

[0116] The reinforcing fiber is a modified steel fiber; the water reducer is a high-efficiency polycarboxylate water reducer.

[0117] The modified steel fiber is prepared by the following steps:

[0118] (1) mixing nano carbon black, silane coupling agent and water in a mass-volume ratio of 0.5 kg: 1 L: 3 L and ultrasonically dispersing for 30 minutes at an ultrasonic dispersion power of 300-350 W to obtain a modified solution;

[0119] (2) The steel fiber was immersed in a 2 mol / L sulfuric acid solution at a solid-liquid ratio of 1:3 to remove impurities, and then fully immersed for 1-2 hours and then washed with deionized water;

[0120] (3) The steel fiber obtained in step (2) is immersed in an ethanol solution with a mass concentration of 50%, and the modified solution in step (1) is added. The modified solution is dispersed and adsorbed on the steel fiber by magnetic stirring at 100 r / min for 10 min. The solution is placed at a high temperature of 120° C. for reaction for 2-3 h, and then cooled to room temperature to obtain the modified steel fiber.

[0121] The particle size of the nano carbon black is 60nm; the length of the steel fiber is 8-10mm and the diameter is 0.18-0.23mm; the solid-liquid ratio of the steel fiber, ethanol solution and modified solution in step (3) is 1kg:3L:3L.

[0122] A method for preparing high-strength permeable concrete comprises the following steps:

[0123] (1) preparing modified steel fiber and preparing toughening and thickening agent according to the proportion;

[0124] (2) Cement, mineral powder and water are mixed and stirred evenly, and then basalt crushed stone, ceramsite, water reducing agent and modified steel fiber are added in sequence and stirred evenly, and finally a toughening and thickening agent is added and stirred evenly to obtain a final product of high-strength permeable concrete.

[0125] Compared with Example 3, this comparative example has the same raw materials and steps as Example 3 except that yellow dextrin is not added as the toughening and thickening agent.

[0126] Performance Testing

[0127] Mechanical properties test: According to the method specified in GB / T 50081.2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the compressive strength and flexural strength of the permeable concrete prepared in Examples 1-3 and Comparative Examples 1-4 were tested.

[0128] Water permeability test: water permeability coefficient and porosity were tested on the permeable concrete prepared in Examples 1-3 and Comparative Examples 1-4 according to the method specified in CJJ / T135-2009 "Technical Specification for Permeable Cement Concrete Pavement".

[0129] The performance test results of each group of permeable concrete are shown in Table 1.

[0130] Table 1 Performance test table of each group of permeable concrete

[0131]

[0132] It can be seen from the data in Table 1 that the permeable concrete prepared by Examples 1-3 of the present invention has excellent compressive strength and flexural strength while maintaining water permeability, indicating that the concrete prepared by the present invention has excellent high-strength water permeability; in addition, the concrete prepared by Examples 1-3 has good frost resistance, indicating that the concrete of the present invention has good durability. Compared with Example 3, although the water permeability of the comparative concrete of Comparative Examples 1-4 is slightly higher than that of the embodiment, the mechanical strength is much lower than that of Example 3, indicating that the modified steel fiber and toughening thickener can improve the compressive strength and flexural strength of concrete. In addition, compared with Example 3, the frost resistance of Comparative Examples 2-4 is far less than that of Example 3, indicating that the thickening and toughening agent of the present invention can improve the durability of concrete. High-strength permeable concrete can be prepared by combining modified steel fiber and toughening thickener and then mixing with other raw materials. Changing any one of the raw material compositions in the raw material formula cannot achieve the same technical effect.

[0133] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

Claims

1. A high-strength permeable concrete, characterized in that: The raw materials include: 1200-1300 parts of basalt crushed stone, 200-220 parts of cement, 300-350 parts of cement, 100-110 parts of water, 70-80 parts of mineral powder, 52-64 parts of reinforcing fiber, 12-16 parts of toughening and thickening agent, and 1.5-3 parts of water reducing agent.

2. The high-strength permeable concrete according to claim 1, characterized in that: The particle size of the basalt gravel is 10-15 mm; The ceramsite is shale ceramsite with a particle size of 5-10 mm.

3. The high-strength permeable concrete according to claim 1, characterized in that: The toughening and thickening agent includes tripropylene glycol methyl ether, hydroxyethyl acrylate and yellow dextrin, and the solid-liquid ratio of the three is 1L:1L:1kg.

4. The high-strength permeable concrete according to claim 1, characterized in that: The reinforcing fiber is a modified steel fiber; the water reducer is a high-efficiency polycarboxylate water reducer.

5. The high-strength permeable concrete according to claim 4, characterized in that: The modified steel fiber is prepared by the following steps: (1) mixing and dispersing nano carbon black, a silane coupling agent, and deionized water to obtain a modified solution; (2) The steel fiber was immersed in a 2 mol / L sulfuric acid solution at a solid-liquid ratio of 1 kg:3 L to remove impurities, and then fully immersed for 1-2 h and then washed with deionized water; (3) The steel fiber obtained in step (2) is immersed in an ethanol solution with a mass concentration of 50%, and the modified solution in step (1) is added, and stirred to allow the modified solution to be dispersed and adsorbed on the steel fiber, and placed at a high temperature of 120° C. to react for 2-3 hours, and then cooled to room temperature to obtain the modified steel fiber.

6. The high-strength permeable concrete according to claim 5, characterized in that: In the step (1), the mass-volume ratio of the nano carbon black, the silane coupling agent and the deionized water is (0.3-0.5) kg:1 L:(1-3) L; and the particle size of the nano carbon black is 60 nm.

7. The high-strength permeable concrete according to claim 5, characterized in that: In the step (3), the solid-liquid ratio of the steel fiber, the ethanol solution and the modified solution is 1kg:3L:3L.

8. The high-strength permeable concrete according to claim 5, characterized in that: The dispersion treatment in step (1) is ultrasonic dispersion for 15-30 minutes, and the ultrasonic dispersion power is 300-350w.

9. The high-strength permeable concrete according to claim 5, characterized in that: The stirring in step (3) is magnetic stirring, stirring at 100 r / min for 10 min.

10. A method for preparing the high-strength permeable concrete according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: (1) preparing modified steel fiber and preparing toughening and thickening agent according to the proportion; (2) Cement, mineral powder and water are mixed and stirred evenly, and then basalt crushed stone, ceramsite, water reducing agent and modified steel fiber are added in sequence and stirred evenly, and finally a toughening and thickening agent is added and stirred evenly to obtain a final product of high-strength permeable concrete.